Variable structure control for an isolated boost converter used in fuel cell applications - S. Vijaya Madhavi; G. Tulasi Ram Das (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In recent years fuel cells have become prominent as an alternative source of energy to meet the society’s energy requirements. A control strategy derived from variable structure theory known as Sliding Mode Control (SMC) was proposed for an Isolated Boost topology which was mostly used in fuel cell systems. Converter operation and its detailed mathematical modelling are also presented. Then the converter with the control strategy suggested is simulated in MATLAB/SIMULINK and compared with other controllers. The results show that transient response of the converter is very fast and steady state error is reduced throughout the load change period with proposed control topology.